View of Qigong and his position in Shaolin Kung Fu in terms of training in the EU, respectively, Czech Republic - Martin Dlouhý; Vladimír Pavlík; Karol Gőrner; Marie Blahutková (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2018)
The aim of the paper is to explain the specific structure of training (not only in the Czech Republic), its characteristics and its principles. It will also be useful to include some new, hitherto carefully hidden - also to point out and highlight some as-yet unpublished inside information about some specific training concepts of this martial art. An integral part of this training is to develop the internal energy called Qigong and some specific techniques within the different levels of performance in Kung Fu. Qigong is an effective part of alternative and natural medicine (and not only) in Shaolin Kung Fu and contribution highlights the need for the necessary representation of Qigong in Shaolin Kung Fu. Part of the contribution is also an aspect of the philosophy of martial arts Shaolin Kung Fu and its relationship to other martial arts.   RESUMO O objetivo do artigo é explicar a estrutura específica de treinamento (não apenas na República Tcheca), suas características e seus princípios. Também será útil incluir alguns novos, até então cuidadosamente escondidos - também para destacar algumas informações ainda não publicadas sobre alguns conceitos específicos de treinamento dessa arte marcial. Uma parte integrante deste treinamento é desenvolver a energia interna chamada Qigong e algumas técnicas específicas dentro dos diferentes níveis de desempenho no Kung Fu. O Qigong é uma parte efetiva da medicina alternativa e natural (e não apenas) no Shaolin Kung Fu e a contribuição destaca a necessidade da representação necessária do Qigong no Shaolin Kung Fu. Parte da contribuição é também um aspecto da filosofia das artes marciais Shaolin Kung Fu e sua relação com outras artes marciais.